Serological evidence of Brucellosis in selected gaushalas of Haryana - SAIDU, A S; MAHAJAN, N K; SINGH, MAHAVIR; MITTAL, DINESH; YOGESH, BANGAR; CHHABRA, RAJESH (The Indian Journal of Animal Sciences, 2020)
Brucellosis is a neglected zoonotic disease with significant economic and public health consequences to human and animal population in developing countries. The objective of the present study was to determine the serological evidences of brucellosis in cattle reared in two gaushalas of Hisar and Jind districts, Haryana. The serological tests: Rose Bengal Plate Test (RBPT), Serum Agglutination Test (SAT) and Enzyme Linked Immunosorbent Assay (ELISA) were employed for screening the animals for brucellosis. The overall seropositivity by RBPT, SAT and ELISA was 23.46%, 20.67% and 28.49% respectively. The logistic regression modalities concluded higher likelihood of brucellosis with age > 6 years followed by 3–6 year than cows with